Literature in a "Digital Ecology": Interdisciplinary Digital Collaboration in Contemporary English Canadian Literature - Griffin-Merth, Shannon (Université d'Ottawa / University of Ottawa, 2025)
This project delineates an emerging genre of cross-disciplinary, geographically located, collaboratively produced Canadian digital literature in English. Drawing on thinking from the fields of new materialism, the digital humanities, architectural theory, cultural geography, and ecology, this dissertation applies a whole systems approach to four recent works in order to highlight a generic impulse toward the emergent, the indeterminate, and the provisional - what Doreen Massey calls "[l]oose ends and ongoing stories." By mapping this impulse across these projects, this dissertation examines the spatial, structural, and infrastructural ecologies they embody, tracing their emergent patterns and reading in them a broader generic concern with social, economic, and environmental inequities. The works this project studies are Canadian, but their interactive digital form extends their relevance and potential impact beyond national borders. Throughout this project, I argue that these works engage audiences in multi-sensory, interactive reading environments, producing localized, participatory readers more attuned to the ecological, economic, industrial, and cultural complexities of the real places they examine and to the creative navigation of the challenges marking our current geological era. This dissertation is divided into four chapters, each of which examines a recent spatial, structural, and infrastructural ecology attending to the material and the ephemeral. The first chapter posits that, by way of its interactive multimodality, Sachiko Murakami's Project Rebuild leads readers into a generative contingency, privileging not established patterns or fixed structures but instead a generous fluidity that makes space for more equitable social, material, and economic relations in urban Canada. The second chapter examines Aaron Tucker et al.'s Loss Sets, which, I argue, generates a productive textual lacuna that forces audiences to read the gaps and omissions forming the compositional substance of the project. The third chapter turns to Madeleine Thien's Vancouver of the Mind, which, I suggest, approaches Vancouver's historic and ongoing displacements and dispossessions by formal and structural means, applying the logic of digital multidisciplinarity and invited collaboration to its examination of the gaps, absences, and injustices occurring in and emerging from its spatial referent. The final chapter argues that in Fred Wah and the High Muck a Muck Collective's High Muck a Muck: Playing Chinese: An Interactive Poem, rivers, migratory routes, mountain ranges, and other arterial forms work in conjunction with the project's multimodality to materialize relational structures and cultivate in audiences a proprioceptive approach to the reading process, strengthening their sense of the connective tissue which binds them to the places, spaces, and structures of the world. In applying a macroecological lens to this emerging genre, and acknowledging the broad readership such digital works invite, this project aims to build a set of observational tools and to cultivate a responsive relationality with the systems and patterns running through the works I study and the places and structures they represent.
Keywords: Canadian literature; digital literature; new materialism; ecocriticism; interdisciplinarity; Indigenous knowledges; Anthropocene; ecopoetics; ruination; architecture; geography; ontology; macroecology; cartography; digital humanities; collaboration; ecology; history; urban studies